Patellar cartilage volume of the back leg versus the higher loaded front leg in current elite male english cricket fast bowlers - Jones, M; Palmer, A; Leyland, K; Peirce, N; Lewis, M; Kerslake, R; Glyn-Jones, S; Newton, J; Arden, N (Elsevier, 2016)
The aim of this study was to determine if the fast bowling action in cricket causes a positive adaptive response to increase patellar cartilage volume in the higher loaded front leg versus the back leg.